Fully quantal treatment of nonadiabatic molecular photodynamics: general considerations and application to the benzene cation - Scheit, Simona; Goswami, Sugata; Meyer, Hans-Dieter; Köppel, Horst (Computational and theoretical chemistry, 2019)
The merits and drawbacks of a mixed quantum-classical description of nuclear motion on coupled potential energy surfaces are discussed and compared with a fully quantal treatment. For the latter a particular approach is highlighted in which an efficient wavepacket propagation scheme, the Multiconfiguration Time-Dependent Hartree (MCTDH) method, is combined with a versatile modeling of the Hamiltonian for interacting potential energy surfaces, the linear vibronic coupling (LVC) model. As an illustrative example this fully quantal treatment is applied to the benzene radical cation, where nuclear motion on five multiply intersecting potential energy surfaces with up to eleven nuclear degrees of freedom has been studied. The results for the electronic population dynamics allow to understand recent pump-probe spectra with ultrashort XUV and visible/near IR laser pulses in terms of few-fs population transfer at two consecutive conical intersections.
Gesehen am 26.07.2019